Early mortality and complications following first-time catheter ablation of atrial fibrillation in a nationwide cohort. (19th May 2022) - Witt, C; Jacobsen, PK; Johannessen, A; Sandgaard, NCF; Gang, UJO; Hansen, PS; Worck, R; Riahi, S; Nielsen, JC; Kristiansen, SB
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF) is the most common clinical arrhythmia. Pulmonary vein isolation (PVI) by catheter ablation has become a cornerstone in the treatment of AF. Serious complications to PVI have been reported to be at an acceptable level and risk of death after AF ablation is low. Purpose: In a contemporary nationwide cohort of patients undergoing first-time PVI by catheter ablation, we wanted to investigate the 30-day mortality after ablation, and to examine risk and potential risk factors of PVI-related complications. Methods: Population-based cohort study in patients who underwent first-time PVI by catheter ablation between 2011-2018 identified from the National Danish Ablation Registry. Primary outcome was early post-procedural mortality, defined as death of any cause within 30 days of index PVI procedure, or in connection to a hospitalization started within 30 days. Secondary outcomes were all-cause rehospitalization and complication, including postoperative infection, cardiac, vascular, neurological, vascular, and pulmonary complications within 30 days. Data on mortality and complications were collected from national health and administrative registries. Binary regression was used to estimate risk ratio (RR) with 95% confidence intervals (CI) for association between selected predictors and any complication, and adjusted gender, age, BMI, prior ablation, calendar period (ablation from 2011-2013, 2014-2016, and >2016). Results: We included 8560 patients. Median age was 62, 66% were men, 12% had a history of heart failure, and median CHA2DS2VASc score was 1 (Interquartile range [IQR]; 1-2). Charlton Comorbidity index (CCI) was none in 66%, moderate in 29% and severe in 5%. A total of 10 (0.12%) patients died within 30 days of ablation, of which 4 patients died during initial hospitalization. Median time to death was 20 (IQR, 12 to 29) days. Patients who died were more likely to have experienced a procedure-related complication (40% vs. 4%, P<0.001). Procedure-related complications occurred in 298 (3.5%), and the risk was 4.4%, 3.0% and 3.3% in the time periods between 2011-2013, 2014-2016 and >2016, respectively. Most common complications were postoperative infection (26%), cardiac complication (26%), and vascular complications (18%). Complication risk was increased in patients with higher age (aRR, 65-74 year; 1.67 [1.32-2.11] and >74 years; 2.48 [1.60-3.84]), moderate CCI (aRR 1.45 [1.14-1.83]), cardiovascular disease (aRR 1.52 [1.09-2.11]) and antithrombotic treatment (aRR 1.41 [1.05-1.89]). After first-time PVI, 1.963 (23%) patients were re-hospitalized within 30 days, and most common primary discharge diagnoses were AF (87%) and direct cardioversion was performed in 765 (39%) patients. Conclusion: In a nationwide cohort of patients who underwent first-time PVI, number of deaths within 30 days of ablation was low (0.12%). Risk of complication was low and 23% of the patients were re-hospitalized within 30 days.